The European multiple patent defendants rule as a legal constraint for start-ups and growth companies - Rantasaari Krista (Oxford University Press, 2022)
The aim of this article is to compare the multiple defendants rule in the unitary patent regime with the Brussels I Regulation and to explore how the multiple defendants rule works under the unitary patent regime for start-up and growth companies.
The unitary patent system with the establishment of the Unitary Patent Court (UPC) will lead to unitary patents covering most European Union countries with a common enforcement mechanism. This also applies to the multiple defendants rule and amends the current legal state. One potential concern related to the multiple defendants rule under the unitary patent regime is the increasing abusive litigation by non-practizing entities (NPEs). NPEs are interested suing multiple defendants due to the cost-efficiency. Even though start-up and growth companies often have less capital, they might be targets of NPE suits.
The article evaluates the current Brussels I Regulation, the relevant case law of the Court of Justice of the European Union and the unitary patent regime from this perspective. The main conclusion of the article is that the multiple defendant rule under the unitary patent regime seems to be an accessible enforcement mechanism for start-ups and growth companies.